Modeling suitable habitats of maleo (Macrocephalon maleo sal. müller 1846) in Gorontalo - Andriwibowo, Andriwibowo; Maarif, Fadjri (Jurnal Penelitian Kehutanan Wallacea, 2023)
Maleo (Macrocephalon maleo) is one of the endangered bird species in Indonesia. This avifauna species is an endemic bird to Sulawesi Island. It is distributed from the south to the north of Sulawesi, including Gorontalo. Currently, information on suitable habitat models for M. maleo is very limited, while this information is required to support the conservation of M. maleo. This study aimed to model the potential habitat for M. maleo using species distribution modeling (SDM) with vegetation cover variables as predictors. The model was built based on the M. maleo occurrence points. The suitable habitat was then evaluated using area under the curve analysis and the receiver operating characteristic curve (AUCROC). Based on the model, the AUC is valued at 0.729, which is considered reasonable and indicates that the model can be used to depict the potential habitats for the species. In this study, most of the west and east parts of Gorontalo were considered not suitable for Maleo. While the coastal areas of Gorontalo were considered very suitable. This was confirmed for both the north and south coastal areas of Gorontalo. Then it is strongly recommended to conserve and protect most of those coasts to ensure the Maleo conservation.